2019
DOI: 10.1155/2019/6873840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tailings Gradation on Rheological Properties of Filling Slurry

Abstract: The key technology in filling mining is the gravity transportation of high-density slurries, and the filling system design is a significant part of this technology. The filling effect depends on the fluidity of the filling slurry. To investigate the influence of the gradation of tailings on the rheological properties of the filling slurry, this study uses particle size analysis to prepare three types of tailings: powder-, relatively fine-, and fine-grained tailings, which are then mixed in different proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…change in microstructure due to restoration and reorganization of interparticle bonds, resulting in strength gain over longer resting times. A similar kind of observation was reported for red mud (Nguyen and Boger, [76], bentonite suspensions gold, copper, and iron tailings [78], and gold tailings [41]. For validation purpose, the results of Nguyen and Boger [76], who produced similar curves on the red mud, are superimposed.…”
Section: Time-dependent Behaviour Of Bauxite Residuesupporting
confidence: 61%
See 1 more Smart Citation
“…change in microstructure due to restoration and reorganization of interparticle bonds, resulting in strength gain over longer resting times. A similar kind of observation was reported for red mud (Nguyen and Boger, [76], bentonite suspensions gold, copper, and iron tailings [78], and gold tailings [41]. For validation purpose, the results of Nguyen and Boger [76], who produced similar curves on the red mud, are superimposed.…”
Section: Time-dependent Behaviour Of Bauxite Residuesupporting
confidence: 61%
“…Validating these statements, Coussot et al [29] observed an increase in yield stress on successive addition of coarser particles to the granular suspension, and Sosio and Crosta [40] noticed changes in the magnitude of rheological properties and rheological behaviour from shear thinning to shear thickening on expanding the particle sizes. On similar lines, Wang et al [41] concluded that the addition of powder-grained gold tailings particles above 40% can result in an increase in yield stress of the gold tailings. Nguyen et al [33] identified that when the percentage of clay fraction is 5-30% range in sand-clay mixtures, yield stress and viscosity increase exponentially, and change in moisture content shows prominent influence than the clay fraction on rheological properties.…”
Section: Introductionmentioning
confidence: 86%
“…In terms of the CL-20/AP/GAP propellant slurries with a given solid content of 65%, the frictional interaction between particles becomes the main factor influencing the rheological properties, while the thermal motion and the repulsive forces of particles are negligible. 24 When particle gradation technology is applied, potential effects are listed as follows: 10 , 25 (1) the finer particles with smooth surfaces act as the lubricant at the contact of particles, which can effectively weaken the frictional interactions between particles with sharp edges, and (2) the step-filling effect of micron-sized, ultrafine, and submicron-sized particles contributes to dense packing, resulting in a decrease in the content of liquids trapped in interparticle spaces, which is not conducive to the slurry flow. Hence, an attempt can be made to illustrate and evaluate the differences in the rheological properties of the slurries in terms of factors affecting the interparticle frictional interactions and particle packing density.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the |η*|-values are effectively reduced to a level that differs inconspicuously from that of the slurries where only AP is included. It follows that the size gradation of CL-20 is a valuable option for promoting the processability of the propellant slurries.In terms of the CL-20/AP/GAP propellant slurries with a given solid content of 65%, the frictional interaction between particles becomes the main factor influencing the rheological properties, while the thermal motion and the repulsive forces of particles are negligible 24. When particle gradation technology is applied, potential effects are listed as follows:10,25 (1) the finer particles with smooth surfaces act as the lubricant at the contact of particles, which can effectively weaken the frictional interactions between particles with sharp edges, and (2) the step-filling effect of micron-sized, ultrafine, and submicron-sized particles contributes to dense packing, resulting in a decrease in the content of liquids trapped in interparticle spaces, which is not conducive to the slurry flow.…”
mentioning
confidence: 99%
“…e open stope mining method is the most widely used underground mining method because of its high production capacity, but it has led to the creation of numerous goafs, which can cause serious safety problems, such as surface subsidence, rock bursts, and strata movement [1,2]. e filling mining method is usually adopted to handle the mined-out areas with tailings.…”
Section: Introductionmentioning
confidence: 99%